2020
DOI: 10.3126/ajms.v11i2.27203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver enzymes and sonological grading in nonalcoholic fatty liver

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of diffuse liver disease with a global prevalence of 25.24% and progresses to fibrosis and nonalcoholic steatohepatitis (NASH). Diagnosing NAFLD requires demonstration of increased liver fat and ultrasound imaging is widely used for screening. Specific blood tests to diagnose NAFLD and NASH are not yet available and alanine transaminase (ALT) has been used as a marker in population based studies. Aims and Objective: This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In our study, a significant association was observed between patients with no related symptoms and advanced grading of NAFLD (p=0.02). Consistently, Armstrong et al 39 study in UK revealed that high proportion of patients with advanced grading of NAFLD were asymptomatic.…”
Section: Discussionsupporting
confidence: 53%
“…In our study, a significant association was observed between patients with no related symptoms and advanced grading of NAFLD (p=0.02). Consistently, Armstrong et al 39 study in UK revealed that high proportion of patients with advanced grading of NAFLD were asymptomatic.…”
Section: Discussionsupporting
confidence: 53%
“…Similar findings were found in study done in Manipal. 11 This study revealed that SGPT and SGOT were the only liver enzyme showing statistically significant difference in between NAFLD (p = 0.02, p = 0.03) suggesting the level of enzyme increased significantly with higher grades of NAFL. Similar association was seen in the study done by Saxena in India.…”
Section: Discussionmentioning
confidence: 60%
“…The convenience sampling method was used and the sample size was calculated using the formula, Sample size (N) = Z 2 pq/e 2 ; Where Z = 1.96 at 95% confidence level; p = 0.3412 (34.12%) 11 ; q = 1-p = 0.6588; e = 0.09 (9% margin of error). The total sample size calculated was 106.60 ≈ 107.…”
Section: Methodsmentioning
confidence: 99%
“…A study with 85 subjects concluded that women (65.88%) had a higher incidence of NAFLD than men (34.12%). Only ALT revealed a significant variation across grade 1 and grade 2 NAFLD (p=0.027) 19 . However, the current study had no significant variation acorss the grades, but significant difference was seen between the controls and the NAFLD grades.…”
Section: Discussionmentioning
confidence: 97%